Forest Fragments, Lemur Communities and Local Perception of Nature in a Protected Area of Northwestern Madagascar - Simmen, Bruno; Harpet, Claire; Hladik, Annette; Edmond, Roger; Pioch, Charlotte; Combo, Ashouraffi S.; Andriaholinirina, Nicole; Ranarijaona, Hery Lisy Tiana; Randriamanana, Lantotiana M. E.; Chambon, Mouna; Li, Tian; Rasoamanantenaniaina, Camelia; et al. (Frontiers in Ecology and Evolution, 2022)
Biological conservation projects conducted in inhabited areas are often based on the combination of ecological diagnostics and study of practices and use of the environment by local communities. They less frequently integrate the influence of the perception and representation of nature on these practices, while these should also be taken into account in the initiation of sustainable conservation actions. We carried out a long-term study combining biological and social science approaches in North-western Madagascar in the Antrema protected area (with dry forest / savannah / coastal ecosystems), including an analysis of the use and perception of nature by its inhabitants. . Together with the study of tree diversity, forest structure and biomass in 7 forest fragments, we estimated population densities of whole communities of diurnal and nocturnal lemurs, one of which is considered sacred. We interviewed local resource users from several villages using classical methods of social anthropology supplemented with perception tests derived from sensory evaluation methods. The structure of forest fragments as well as their basal area and richness in tree species varied with human pressure on specific plants (timber extraction) or with historical changes in pasture management (forest regrowth). Lemurs were generally abundant, with a high total biomass compared to other dry forests. Although the inhabitants of Antrema (Sakalava, Tsimihety and Betsileo) still strongly adhered to local use rights and shared deeply rooted knowledge about the forest, the use and perception of nature (e.g. regarding the sacred lemur Propithecus coronatus) have changed since the Antrema protection project in 2000. The results suggest that local communities tend to integrate traditional rules about nature with international environmental regulation, perhaps a sign of a new ecological awareness. However, in the new management mode accompanying this transition, it can also be a means of local empowerment that takes advantage of a program supporting pro-environmental management of the Antrema area.